Child discourse - Ervin-Tripp, Susan M. (Susan Moore), 1927-2018; Mitchell-Kernan, Claudia (Language, thought, and culture., 1977)
Child Discourse contains papers presented in a symposium on child discourse at the annual meeting of the American Anthropological Association in Mexico City in November 1974. Three other papers, one presented by Edelsky at the same meeting, and two by Dore and Garvey, are also included to broaden the scope of methods and issues considered.